(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The gems and jewellery industry is broadlydivided into three main categories, which includes cut and polished diamond,gold jewellery, precious and semi-precious stones. The two major segment of theGems & Jewellery business in Surat are gold jewellery and diamondjewellery. While a predominant portion of gold jewellery manufactured in Suratis for domestic consumption; a major portion of rough, uncut diamonds processedin India in the form of either polished diamonds or finished diamond jewelleryis exported. Gold jewellery accounts for around 80% of the Indian jewellerymarket; with the balance comprising of fabricated studded jewellery-diamondsand gemstones. Diamond holds the most important position in terms of foreignexchange earnings. Processed diamonds contribute about 80% of the total exportof the industry, which makes the Indian gems and jewellery industry diamondcentric. India accounts for nearly 55% of world net exports of cut and polisheddiamonds in value terms. There is hardly any other export segment of thecountry that has such a significant share in the world market.